A Quality Improvement Approach to Reduce Unplanned Extubation in the NICU While Avoiding Sedation and Restraints. Issue 5 (September 2020) - Bertoni, C. Briana; Bartman, Thomas; Ryshen, Gregory; Kuehne, Brandon; Larouere, Marissa; Thomas, Leslie; Wishloff, Erin; Shepherd, Edward; Dillard, Julie; Pavlek, Leeann R.; Moallem, Mohannad
Abstract : Introduction: The unplanned extubation (UE), a common adverse event in the neonatal intensive care unit (NICU), may result in airway trauma, cardiopulmonary resuscitation, and, in extreme cases, death. As part of the Nationwide Children's Hospital NICU's effort to optimize NICU graduates' neurodevelopmental outcomes, skin-to-skin care of intubated infants is encouraged, while sedation and restraints to prevent UE are strongly discouraged. This project aimed to decrease the UE rate from 1.85 to 1.5 per 100 endotracheal tube (ETT) days. Methods: The project occurred in a 114-bed, level-IV NICU with approximately 850 admissions per year and 100% outborn infants. A multidisciplinary team began biweekly meetings to review all UE events, later separating these into preventable and nonpreventable. Important ongoing tests of change included assigning a single process owner for UE reporting, ensuring proper ETT securement, and using 2 clinical staff during patient and/or ETT manipulation. Results: Early in the project, enhanced detection led to an increased rate from 1.85 to 3.26 per 100 ETT days. However, identifying preventable events empowered staff to decrease the frequency to 2.03 per 100 ETT days. In August 2017, an ETT taping method change produced an increase in special causes due to decreased compliance. However, when securement methods were enhanced, noncompliance reversed and is now trending favorably. Conclusions: Decreasing UE in a neurodevelopmentally friendly unit, which avoids sedation and restraints, is challenging. Using a multidisciplinary quality improvement approach and after appropriately capturing events, we reduced UE, with the highest impact of intervention being ETT securement standardization. Abstract : Supplemental Digital Content is available in the text.